2011
DOI: 10.1175/jcli-d-10-05006.1
|View full text |Cite
|
Sign up to set email alerts
|

The Threshold Sea Surface Temperature Condition for Tropical Cyclogenesis

Abstract: The analyzed value of sea surface temperature (SST) is examined for all global cases of tropical cyclone formation within 358 latitude of the equator over the period 1981-2008. It is found that 98.3% of formations occur at SST values exceeding 25.58C. This practical threshold is relatively insensitive to the exact value of maximum wind speed used to define formation. The threshold is sensitive, however, to short-term variations in SST during development. By expanding the time period such that thresholds are ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(46 citation statements)
references
References 16 publications
6
40
0
Order By: Relevance
“…Recently, Dare and McBride (2011) indicated that 98.3% of tropical cyclogenesis occurs at SST values exceeding 25.5 C. This observation is particularly relevant to our study because mean annual SST was well below 24 C prior to 13 ka BP and the threshold was reached by 12.5 ka BP. By 13 ka BP, SST had already reached 25 C; then increased to 27 C by 12.5 ka BP, and remained within a range of 2 C on either side of 27 C (see Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Recently, Dare and McBride (2011) indicated that 98.3% of tropical cyclogenesis occurs at SST values exceeding 25.5 C. This observation is particularly relevant to our study because mean annual SST was well below 24 C prior to 13 ka BP and the threshold was reached by 12.5 ka BP. By 13 ka BP, SST had already reached 25 C; then increased to 27 C by 12.5 ka BP, and remained within a range of 2 C on either side of 27 C (see Fig.…”
Section: Discussionsupporting
confidence: 56%
“…Gray 1968;Holland 1997) as a threshold SST for the formation of TCs. This threshold temperature was recently revisited by Dare and McBride (2011) using observations from 1981 to 2008 with results consistent with these earlier studies. They found that the majority (93%) of TCs occur at SSTs greater than 26.5°C and over 98% at SSTs greater than 25.5°C.…”
supporting
confidence: 56%
“…The average predicted increase in wind storm losses in Europe is +8 % per degree Celsius of warming. Because the climate system is highly nonlinear (Dare and McBride 2011;Bender et al 2010;Knutson et al 2010), there is no a priori reason to expect that the per-degree effect of temperature on losses is the same for small and large changes in temperature. To explore whether there may be nonlinearities, Columns (2) and (3) of Table 3 present the distribution of treatment effects for climate change scenarios that involve changes in temperature less than 2°C, and greater than or equal to 2°C, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Tropical cyclone development and power dissipation is a nonlinear, dynamic process that depends on whether sea surface temperatures (SST) exceed 26.5°C, as well as on SST gradients, vertical wind shear, atmospheric stability, and other factors (Dare and McBride 2011;Bender et al 2010;Knutson et al 2010). Anthropogenic climate change is likely to cause increases in SST, but is not expected to cause continuously increasing SST gradients, resulting in ambiguous predicted net effects on tropical cyclone power dissipation (IPCC, 2012).…”
mentioning
confidence: 99%